Electrophysiology of human cardiac atrial and ventricular telocytes. Issue 2 (February 2014) - Sheng, Jingwei; Shim, Winston; Lu, Jun; Lim, Sze Yun; Ong, Boon Hean; Lim, Tien Siang; Liew, Reginald; Chua, Yeow Leng; Wong, Philip
Abstract Telocytes (TCs) with exceptionally long cellular processes of telopodes have been described in human epicardium to act as structural supporting cells in the heart. We examined myocardial chamber‐specific TCs identified in atrial and ventricular fibroblast culture using immunocytochemistry and studied their electrophysiological property by whole‐cell patch clamp. Atrial and ventricular TCs with extended telopodes and alternating podoms and podomers that expressed CD34, c‐Kit and PDGFR‐β were identified. These cells expressed large conductance Ca2+‐activated K+ current (BKCa) and inwardly rectifying K+ current (IKir), but not transient outward K+ current (Ito) and ATP‐sensitive potassium current (KATP). The active channels were functionally competent with demonstrated modulatory response to H2S and transforming growth factor (TGF)‐β1 whereby H2S significantly inhibited the stimulatory effect of TGF‐β1 on current density of both BKCa and IKir. Furthermore, H2S attenuated TGF‐β1‐stimulated KCa1.1/Kv1.1 (encode BKCa) and Kir2.1 (encode IKir) expression in TCs. Our results show that functionally competent K+ channels are present in human atrial and ventricular TCs and their modulation may have significant implications in myocardial physiopathology.